Transcranial stimulation of the human primary motor cortices - Bachtiar, VE (2015)
The primary aim of this thesis is to investigate the physiological effects of transcranial direct current stimulation (tDCS) as applied to the primary motor cortex (M1). This research was largely motivated by the need to understand the basic physiological changes of tDCS, in order to evaluate its use as a potential tool in recovery after stroke, as well as its more general applicability as a tool to modulate plasticity. The experiments in this thesis assess the ability of tDCS to modulate the primary motor cortex in healthy controls. The effects of tDCS on cortical GABA and motor resting state functional connectivity were measured with magnetic resonance spectroscopy (MRS) and resting functional MRI (fMRI). Anodal stimulation reduced GABA concentration and increased functional connectivity in the stimulated M1. Testing these changes within the same individuals demonstrated that the magnitude of changes do not correlate across subjects. Novel evidence on the timecourse of GABA change demonstrated that the reduction in GABA is most prominent in the 30-minute period after stimulation. To determine whether the tDCS-induced modulations in inhibition is restricted to the stimulated hemisphere or whether inhibitory changes could be observed in the nonstimulated M1, or in the interhemispheric connections between the M1s, transcranial magnetic stimulation (TMS) was used to measure intracortical inhibition in each M1 and interhemispheric inhibition and facilitation in the contralateral M1. There were no polarity-specifc effects on intracortical inhibition within either M1, and no changes in interhemispheric excitability from the stimulated to non-stimulated M1. Development of a two-voxel MRS method at ultra high field (7 Tesla) allowed for concurrent measurements of cortical neurotransmitters from both M1s with excellent spectral quality and GABA quantifcation. This method was used to demonstrate the timecourse of tDCS-induced changes in neurochemicals concurrently from both M1s. Anodal stimulation reduced GABA in both the anode-targeted and non-stimulated M1. Cathodal stimulation decreased GABA and glutamate in the non-stimulated M1, with no concurrent changes in the cathode-targeted M1. Bilateral stimulation reduced glutamate in both M1 with no change in GABA.